2017
DOI: 10.18632/oncotarget.21835
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis of circular RNAs in prenatal and postnatal muscle of sheep

Abstract: Circular RNAs (circRNAs), a type of non-coding RNA with circular structure, were generated by back splicing and widely expressed in animals and plants. Recent studies have shown that circRNAs extensively participate in cell proliferation, cell differentiation, cell autophagy and other biological processes. However, the role and expression of circRNAs in the development and growth of muscle have not been studied in sheep. In our study, we first used RNA-seq to study the circRNAs in prenatal and postnatal longis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 67 publications
(53 reference statements)
0
36
0
Order By: Relevance
“…De novo discovery of circRNAs is based on the presence of exon-junction spanning reads in RNA-seq datasets; the effective existence of a newly identified circRNA then requires PCR validation with divergent primers and RNase R digestion assay to prove exonuclease resistance. This experimental pipeline has allowed the identification and annotation of hundreds of circRNAs, which are expressed and modulated during cultured myoblasts differentiation (Chen et al, 2018) or in developing and aging skeletal muscle of various mammalian species (Li et al, 2017;Wei et al, 2017) ( Table 4). The high-throughput discovery of this large amount of circular RNAs has boosted the characterization of their biological significance and the molecular mechanisms of posttranscriptional regulation in which they are involved.…”
Section: Circrnas In Skeletal and Cardiac Myogenesismentioning
confidence: 99%
“…De novo discovery of circRNAs is based on the presence of exon-junction spanning reads in RNA-seq datasets; the effective existence of a newly identified circRNA then requires PCR validation with divergent primers and RNase R digestion assay to prove exonuclease resistance. This experimental pipeline has allowed the identification and annotation of hundreds of circRNAs, which are expressed and modulated during cultured myoblasts differentiation (Chen et al, 2018) or in developing and aging skeletal muscle of various mammalian species (Li et al, 2017;Wei et al, 2017) ( Table 4). The high-throughput discovery of this large amount of circular RNAs has boosted the characterization of their biological significance and the molecular mechanisms of posttranscriptional regulation in which they are involved.…”
Section: Circrnas In Skeletal and Cardiac Myogenesismentioning
confidence: 99%
“…CircRNAs have been identified in numerous species, including nematodes, flies, birds, and mammals. Specifically, a recent RNA-seq analysis of circRNAs in striated muscle from different animals showed that they are abundant and dynamically expressed during muscle development and aging [ 55 , 56 , 57 , 58 , 59 , 60 ] ( Table 1 ). As in other tissues, most circRNAs identified in skeletal muscles are exonic (80–90%) and several of them show differential expression between developmental stages [ 57 , 60 ] and different age conditions [ 55 , 57 ].…”
Section: Circular Rnas In Myogenesismentioning
confidence: 99%
“…Recent study has shown that inhibition or slowing of canonical pre-mRNA processing events shifts the output of protein-coding genes toward circular RNAs ( Liang et al, 2017 ). CircRNAs are observed in a diverse range of life forms, including archaea ( Danan et al, 2012 ), mammals such as humans ( Salzman et al, 2012 ), mice ( Jiang et al, 2014 ; Pei et al, 2017 ), mosquitos ( Gruner et al, 2016 ), sheep ( Li et al, 2017 ), and plants such as rice ( Lu et al, 2015 ; Ye et al, 2015 ), Arabidopsis ( Ye et al, 2015 ; Sun et al, 2016 ; Pan et al, 2018 ; Dou et al, 2017 ), barley ( Darbani, Noeparvar & Borg, 2016 ), and maize ( Chen et al, 2018 ). This diversity suggests conserved biological functions and distinct properties.…”
Section: Introductionmentioning
confidence: 99%